Evaluation and correlation of physiological parameters and bioclimatic indexes holstein cows in different seasons. - Avila, André Sanches de; Jácome, Ianglio Márcio Travassos Duarte; Faccenda, Andressa; Panazzolo, Dejani Maira; Müller, Éderson Rogério (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/2236117010747 The objective of this study was to determine the physiological parameters of Holstein cows in milking during the winter and spring season and correlate these parameters with the bioclimatic indexes. We used nine Holstein cows in a completely randomized delimitation in a subdivided plot arrangement with repeated measures in time. Data were collected during the winter and spring, which were measured respiratory rate (RR), heart rate (HR), superficial temperature (ST) and rectal temperature (RT) from animals, besides the air temperature, the relative humidity and black globe temperature. It was calculated the temperature and humidity index (THI), the Black Globe Temperature and Humidity Index (BGTH) and Radiant Heat Load (RHL). The THI, BGTH and RHL showed increases in the afternoon suggesting an environment susceptible to stress. There were no statistical differences (P>0.05) between the seasons of winter and spring for any of the physiological variables. Only HR was above physiological limits for cattle. HR, RR and ST showed significant positive correlation (P<0.01) with the THI and BGTH and RHL. However, heat stress was not detected in animals in the winter and spring seasons, although the physiological parameters have shown a correlation with the bioclimatic indexes.